In vitro and in vivo evaluation of some tablet formulations of Sulfisoxazole - Pandey V.P.; Pandit J.K. (My University, 2025)
A bioavailability study o one commercial and four fabricated tablet formulations of sulfisoxazole was conducted in four (for one formulation three subjects) healthy human volunteers with single oral 1g dose. The possible effect of additives on the urinary excretion pattern of sulfisoxazole was examined. The drug was analysed in urine for 'total' and 'free' forms. Although two fabricated formulation gave significantly lower extent of bioavailability, the other two fabricated tablets were not significantly different from the reference commercial product. The slow rate of absorption for one formulation was observed to be associated with long dissolution time.